How to go green: unraveling green preferences of consumers. Issue 1 (7th April 2015) - Sony, Alisa; Ferguson, David; Beise-Zee, Rian
Abstract : Purpose: – Although a company can manifest its corporate social responsibility (CSR) effort through various strategies, the challenge this presents is that not all CSR activities have identical attributes with respect to the consumers' perception. The purpose of this paper is to examine the efficacy of four CSR initiatives – regulatory compliance, green cause-related marketing (CRM), green product, and a combination of green CRM and green product – on consumer attitude and purchase intention. Design/methodology/approach: – An experiment is conducted to investigate how consumers in an emerging Asian market like Thailand respond to different environmental CSR tactics. Findings: – The results of this study demonstrate that a specific environmental CSR strategy elicits more favorable response than a general approach of complying with regulations. In addition, engaging in green CRM and offering a green product concurrently is perceived as more appealing than employing only either of the two strategies. The key finding is that in the eyes of Thai consumers, green CRM and green product CSR initiatives are substitutable. Originality/value: – The paper conceptualizes the difference between four environmental CSR strategies from dimensions of the firm's discretion and commitment level and highlights the importance of using specific voluntary environmental CSR strategies over involuntary regulatory compliance. Firms are recommended to engage in either green CRM or green product initiatives. The choice depends on a firm's resources and opportunities. The addition of green CSR initiatives increases the positive impact on consumer attitude and purchase intention.